2010
DOI: 10.1093/nar/gkq1155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MBNL1 and MBNL3 domains required for splicing activation and repression

Abstract: Muscleblind-like 1 (MBNL1) is a splicing regulator that controls developmentally regulated alternative splicing of a large number of exons including exon 11 of the Insulin Receptor (IR) gene and exon 5 of the cardiac Troponin T (cTNT) gene. There are three paralogs of MBNL in humans, all of which promote IR exon 11 inclusion and cTNT exon 5 skipping. Here, we identify a cluster of three binding sequences located downstream of IR exon 11 that constitute the MBNL1 response element and a weaker response element i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 41 publications
(75 reference statements)
5
65
2
Order By: Relevance
“…An intriguing possible explanation for this observation is that some MBNL1-mediated splicing events are partially mediated by protein-protein interactions that are important for recruiting MBNL1 to the transcript. Regions outside the ZFs that may be important for mediating such interactions have been recently defined (14). Using RIMs as sensitized backgrounds, we demonstrated that the Q-rich region downstream of ZF2 contributes to ZF3-4 function only in class I events.…”
Section: Figmentioning
confidence: 80%
See 2 more Smart Citations
“…An intriguing possible explanation for this observation is that some MBNL1-mediated splicing events are partially mediated by protein-protein interactions that are important for recruiting MBNL1 to the transcript. Regions outside the ZFs that may be important for mediating such interactions have been recently defined (14). Using RIMs as sensitized backgrounds, we demonstrated that the Q-rich region downstream of ZF2 contributes to ZF3-4 function only in class I events.…”
Section: Figmentioning
confidence: 80%
“…Regions outside the ZFs have recently been hypothesized to be important for MBNL1 splicing activity. Specifically, deletion analysis defined a glutamine-rich region on the C=-terminal end of ZF2 that has been hypothesized to be important for both splicing activation and repression activities (14). The key glutamine (Q) and methionine (M) residues within this region were mutated to alanines to create the MBNL1 Q-mutant (i.e., WT-Q) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3). By contrast, the biological activity (Grammatikakis et al, 2011;Hall et al, 2013) and the expression pattern of Ptb family, as well as Mbnl3, suggest that they are putative repressors of Mef2D a2 exon inclusion in myoblasts (supplementary material Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…We then searched specific sequences for splicing regulation around MYH14 exon 6 and found that there are 3 "YGCU(U/G)Y" motifs and 6 "YGCY" sequences in intron 5 and 6 of the gene. These motifs have been shown to directly interact with the MBNL1 protein and mediate the c-TNT and IR gene alternative splicing (Grammatikakis et al, 2010). MBNL1 could therefore regulate the alternative splicing of the MYH14 gene leading to the missplicing observed in DM1 muscle.…”
Section: Discussionmentioning
confidence: 99%